Relaxation-compensated CEST-MRI of the human brain at 7T: unbiased insight into NOE and amide signal changes in human glioblastoma - Zaiss, Moritz; Windschuh, Johannes; Paech, Daniel; Meißner, Jan-Eric; Burth, Sina; Schmitt, Benjamin; Vollmuth, Philipp; Wiestler, Benedikt; Wick, Wolfgang; Bendszus, Martin; Schlemmer, Heinz-Peter; Ladd, Mark E.; et al. (NeuroImage, 2015)
Endogenous chemical exchange saturation transfer (CEST) effects of protons resonating near to water protons are always diluted by competing effects such as direct water saturation and semi-solid magnetization transfer (MT). This leads to unwanted T2 and MT signal contributions that contaminate the observed CEST signal. Furthermore, all CEST effects appear to be scaled by the T1 relaxation time of the mediating water pool. As MT, T1 and T2 are also altered in tumor regions, a recently published correction algorithm yielding the apparent exchange-dependent relaxation AREX, is used to evaluate in vivo CEST effects. This study focuses on CEST effects of amides (3.5ppm) and Nuclear-Overhauser-mediated saturation transfer (NOE, −3.5ppm) that can be properly isolated at 7T. These were obtained in 10 glioblastoma patients, and this is the first comprehensive study where AREX is applied in human brain as well as in human glioblastoma. The correction of CEST effects alters the contrast significantly: after correction, the CEST effect of amides does not show significant contrast between contrast enhancing tumor regions and normal tissue, whereas NOE drops significantly in the tumor area. In addition, new features in the AREX contrasts are visible. This suggests that previous CEST approaches might not have shown pure CEST effects, but rather water relaxation shine-through effects. Our insights help to improve understanding of the CEST effect changes in tumors and correlations on a cellular and molecular level.
Gesehen am 16.07.2020